Exploring Dehumanization In The Maus Comics By Art Spiegelman - Tegar Tri Surya Kencana; Nurholis Nurholis (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
This study limits the problem its problem to the issue of social dehumanization depicted in the comic Maus, which as a reflection of the Jewish community’s condition in Germany during the Nazi regime. This research is qualitative research that uses Ian Watt's sociology of literature as a basis for theorizing. By regarding literature as a reflection of society, this research aims to elucidate how the comic Maus reflects the issue of dehumanization, based on the social realities of the World War II era. The data used in this study are quotations from the comic Maus, supplemented by supporting literature such as books and scholarly articles. The data collection techniques employed in this research include: 1) identifying social issues within the comic, 2) analyzing and interpreting these social issues, 3) examining the data as a reflection of society depicting the social problem of dehumanization among the Jewish community in Germany during the Nazi regime, and 4) formulating conclusions based on the analysis conducted. The conclusion drawn from this research is that the comic Maus serves as a reflection of the dehumanization in Germany according to the author's perspective or ideology, influenced by the author's social background. As a reflection of social realities, Maus cannot fully represent the entirety of society. Through the author, who represents a segment of society that experienced the Holocaust, Spiegelman presents his social viewpoint on the dehumanization that occurred in Germany, drawing from his family's experiences as survivors of the horrific events perpetrated by the Nazis.